Physical and Physiological Demands of Amateur Portuguese Field and Assistant Football Referees - Ricardo Gomes; Rodrigo Mendes; Amaro Ferreira; Rui Mendes; Gonçalo Dias; Fernando Martins (MDPI AG, 2024)
Referees are crucial elements in football, and they must meet the physical and physiological demands each match poses to them. The aim is to analyse the physical and physiological demands of amateur referees in games at the regional level (4th division), examining the differences between the first and second halves and between assistant (age: 25.10 ± 4.97) and main referees (age: 25.65 ± 5.12). A total of 29 matches were analysed with GPS devices, and internal and external load metrics were analysed. Overall, main referees, due to their central role in game management, showed higher levels of physical and physiological load than assistant referees, with more high-intensity activities, greater distance covered and higher heart rate. The results also revealed that there were no differences between the halves for total distance covered for either the main or assistant referees. However, the main referees covered a greater distance in high-intensity running during the first half (p = 0.05; d = 0.389). These findings emphasise the importance of tailored training protocols to enhance performance and reduce fatigue-related errors, highlighting the significance of endurance, high-intensity running ability, and strategies to manage transient fatigue in referee preparation.